2020
DOI: 10.1186/s12889-020-09683-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of financial incentives on diabetes prevention program attendance and weight loss among low-income patients: the We Can Prevent Diabetes cluster-randomized controlled trial

Abstract: Background Penetration and participation of real life implementation of lifestyle change programs to prevent type 2 diabetes has been challenging. This is particularly so among low income individuals in the United States. The purpose of this study is to examine the effectiveness of financial incentives on attendance and weight loss among Medicaid beneficiaries participating in the 12-month Diabetes Prevention Program (DPP). Methods This is a cluster-randomized controlled trial with two financial incentive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Financial incentives might be also considered as a mechanism to improve engagement in at-risk individuals who are not ready to change behaviors. A community-based randomized controlled trial found that participation in a DPP was significantly higher for participants who received incentives compared to those who did not ( 58 ) and the intervention remained cost-effective even with the provision of direct financial incentives ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Financial incentives might be also considered as a mechanism to improve engagement in at-risk individuals who are not ready to change behaviors. A community-based randomized controlled trial found that participation in a DPP was significantly higher for participants who received incentives compared to those who did not ( 58 ) and the intervention remained cost-effective even with the provision of direct financial incentives ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome is time-to-attrition from the DPP, and secondary outcomes are the percentage of weight change, HbA1C reduction, and mean PA minutes. Time-to-attrition from the DPP is defined as missing two consecutive core sessions and make-up sessions within the Core Session Phase (1-6 months) or missing two consecutive core maintenance sessions and make-up maintenance sessions within the Core Maintenance Phase (7-12 months) (Desai et al, 2020;Cannon et al, 2020). A session is completed when the participant has finalized the lesson's activities and recorded weekly body weight and PA minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the study sample of women was ideal for an intervention to improve dietary and physical activity, with the majority having elevated weights, risk of diabetes, and less healthy diet and physical activity behaviors. The group averaged a level of weight loss across 16 weeks similar to other DPP trials (e.g., [68]). Consistent with the present study, adults with chronic disease risk factors have poorer quality diets [69].…”
Section: Discussionmentioning
confidence: 99%